Pengabdian Masyarakat Pelatihan Eksplorasi Produk Tie Dye Sebagai Produk Suvenir bagi Guru MGMP dan Warga Desa Cisaat Kabupaten Subang - Dewi Suliyanthini; Harsuyanti Lubis; Moehamad Noerharyono; Dian Utari (IKRA-ITH ABDIMAS, 2023)
Exploration training to make tie dye products as souvenir products at Subang tourist sites is anappropriate target for the right target, for residents around Cisaat village and for MGMP teachersthroughout Subang Regency. Tiedye products in the form of rainbow T-Shrit, shibori masks, jumputanguidebags and long sasirangan fabrics, are exploration products from the community service activitiesof the Community Service Institute team - State University of Jakarta, lecturer at the Faculty ofEngineering, Fashion Design Education study program in 2022. The results of this activity MGMPresidents and teachers are motivated, enthusiastic, enthusiastic, from not understanding tounderstanding with skills and knowledge of the tiedye rainbow motif coloring technique. And willspread these knowledge skills to the students of the Subang MGMP teachers